Répertoire bibliographique des livres imprimés en France au seizième siècle - Aquilin, Pierre; Arnoult, Jean-Marie; Baillet, Lina; Benzing, Josef; Betz, Jacques; Desgraves, Louis; Jenny, Jean; Kolb, Albert; Labarre, Albert; Mathieu, Germaine; Muller, Jean; Ronsin, Albert; et al. (Verlag Valentin Koerner GmbH, 2000)
Bibliography of books printed in France in the sixteenth century (apart from Paris, Lyon and Strasbourg) by order of towns, printers and books printed. The results of this research, carefully prepared and accompanied by numerous references, make a very important contribution to the history of the production of printing presses in France in the sixteenth century.